Elections in Europe: A Data Handbook - Nohlen, Dieter; Stöver, Philip (Nomos Verlagsgesellschaft mbH & Co. KG, 2010)
“Elections in Europe” is the eagerly awaited concluding part of a wider project covering electoral data worldwide. It completes the series of volumes focusing on Africa, on Asia and the Pacific, and on the Americas, all published by Oxford University Press. A comparative introduction on elections and electoral systems, given by the editors, is followed by chapters on each European state written by renowned specialists. Applying systematic criteria and uniform concepts to the information that has been collected, each chapter explains the historical, political, and legal context in which elections take place.The chapters also provide exhaustive statistics on all national elections and referendums conducted in the respective countries. Political scientists worldwide welcome this indispensable source for scholars in the field of cross-national political research. There is no comparable work on the subject.“These election volumes are a precious, indispensable source of information for cross-national political research. There is no comparable work on the subject”.Giovanni Sartori, Professor Emeritus, Columbia University, New York“These data handbooks are a wonderfully rich, precise, and comprehensive resource for social scientists and others who do comparative research on elections worldwide. Elections in Europe is a truly monumental and admirable volume!” Arend Lijphart, Professor Emeritus, University of California, San Diego“Elections in Europe constitutes an extraordinary effort. Along with the other volumes in the series it provides a reliable, systematic and analytical source of election data and documentation on electoral systems. An entire discipline will be able to rely on it for years to come. The authors must be congratulated for providing the scientific community with such a valuable instrument”.Daniele Caramani, Professor of Political Science, University of St. GallenContributors: Carsten Anckar, Dag Anckar, Rudy B. Andeweg, Christian Baukhage, Sarah Birch, Christian Bolliger, Mario Caciagli, Terry D. Clark, Dorothée de Nève, Josje Den Ridder, Jørgen Elklit, Michael Gallagher, Marian Gallenkamp, George Gerapetritis, Florian Grotz, Sophia Hänny, Ólafur Th. Hardarson, László Hubai, Galen A. Irwin, Dovil? Jakni?nait?, Mirjana Kasapovi?, Steffen Kassner, Stephanos Koutsoubinas, Gunnar Helgi Kristinsson, Charlotte Larsen Cadoret, Tomáš Lebeda, Wolf Linder, Ralf Lindner, Georg Lutz, Wilfried Marxer, Anna Materska-Sosnowska, Arthur Mickoleit, Neil Munro, Claus Neukirch, Dieter Nohlen, Artis Pabriks, Antonis Pantelis, Klaus Poier, Richard Rose, Marek Rybá?, Astrid Sahm, Henrik Schober, Rainer-Olaf Schultze, Johannes Schwehm, Allan Sikk, Philip Stöver, Pedro Tavares de Almeida, Marc Thiltgen, Antony Todorov, Matthias Trefs, Josep M. Vallès, Visvaldis Valtenbergs, Liam Weeks, Stephen White, Anders Widfeldt, and Andreas M. Wüst.